Distributed Event-Triggered Control for Frequency Restoration in Islanded Microgrids with Reduced Trigger Condition Checking - Yulin Chen; Donglian Qi; Zhenming Li; Zhenyu Wang; Xinyi Yang; Jianliang Zhang (CSEE Journal of Power and Energy Systems, 2024)
For islanded microgrids (MGs), distributed control is regarded as a preferred alternative to centralized control for the frequency restoration of MGs. However, distributed control with successive communication restricts the efficiency and resilience of the control system. To address this issue, this paper proposes a distributed event-triggered control strategy for the frequency secondary control in islanded MGs. The proposed event-triggered control is Zeno behavior free and enables each DG to update and propagate its state to neighboring DGs only when a specific “event” occurs, which significantly reduces the communication burden. Compared with the existing event-triggered control, a trigger condition checking period of the proposed event-triggered control is provided to reduce the computation burden when checking the trigger condition. Furthermore, using the aperiodicity and intermittent properties of the communication, a simple detection principle is proposed to detect and isolate the compromised communication links in a timely and economic fashion, which improves the resilience of the system against FDI attacks. Finally, the control effectiveness of the proposed control scheme is validated by the simulation results of the tests on an MG with 4 DGs.